The Transcription Factor, T-bet, Primes Intestine Transplantation Rejection and Is Associated With Disrupted Mucosal Homeostasis. Issue 4 (April 2015) - Ranganathan, Sarangarajan; Ashokkumar, Chethan; Ningappa, Mylarappa; Schmitt, Lori; Higgs, Brandon W.; Sindhi, Rakesh
<x xml:space="preserve">Abstract</x> Background The transcription factor, t-bet, promotes inflammatory polarization and intestinal homing of many inflammatory cells. In previous studies, the t-bet and granulysin genes were upregulated in peripheral blood before and after intestine transplantation (ITx) rejection, but not during rejection, possibly because of sequestration in allograft mucosa. Mucosal sequestration of t-bet and granulysin may also explain the presence of inflammatory CD14+ monocyte-derived macrophages (MDM) and immunoglobulin G+ B-cell lineage cells, and loss of mature non-inflammatory CD138+ plasma cells in allograft mucosa during ITx rejection in these previous studies. Methodology T-bet–stained and granulysin-stained cells, MDM and CD138+ plasma cells were evaluated with immunohistochemistry in serial biopsies from 17 children, in whom changes in MDM and CD138+ plasma cells were observed previously. Results T-bet–positive mucosal cells were significantly higher in postperfusion (P = 0.035) and early posttransplant biopsies (P = 0.016) among rejectors, compared with nonrejectors. T-bet–positive cell counts per high-power field (hpf) were (a) positively correlated with MDM counts/hpf in postperfusion (Spearman r = 0.73; P = 0.01) and early posttransplant biopsies (r = 0.54, r = 0.046), and (b) negatively correlated with CD138+B-/pre-plasma cells in early posttransplant biopsies (r = 0.63, P = 0.038). T-bet expression in CD14+ monocytes, CD19+B cells, and several other leukocyte subsets was higher in random blood samples from two rejectors, compared with those from five normal human subjects and three nonrejectors. Scant granulysin-stained mucosal cells precluded additional evaluation of this cytotoxin and its role in ITx rejection. Significance The transcription factor, t-bet, primes ITx rejection, and associates with disrupted homeostatic relationships between innate and adaptive immune cells in the allograft mucosa during rejection.